PENERAPAN METODE FIELD TRIP DALAM MENINGKATKAN KEMAMPUAN BERBICARA PADA SISWA KELAS V SD INPRES 2 TANAMODINDI PALU - Nusi, Kurniati (BAHASANTODEA, 2016)
The subject of this research is fifth grade student at SD inpres 2 Tanamodindi Paluin academic year 2015/2016 which amount of 35 students consist of 17 girls student and 18 boys student and involve participants of some sides among them are the teacher of SD inpres 2 Tanamodindi Palu as a partner of the research and observer. The data accumulation was done with using speaking ability test and papersheet observation of student and teacher activity. An action achieved indicator was KKM individual 70 and clasical completeness minimal 80% which individual completeness. The result of this research show that : 1) learning with using field trip method was done with planned and organized through planning activity, implementation, observation and refletion to the excess and weakness field trip method, 2) the teacher activity at the cycle I implemented with well, cycle II is very well and student activity at the cycle I implemented with enough, cycle II imlemented with well, And 3) learning using field trip method to improve speaking ability of the student with achieved was before student speaking ability action of fifth grade student is average 70,26 with clasical achievementÂ is 34,29%; cycle I is average 75,82 with clasical achievement is 68,57%; and cycle II is average 80,05 with clasical achievement is 85,71%.